2022
DOI: 10.1111/1755-0998.13684
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing paralogues for phylogenetic reconstruction has the potential to increase species tree support and reduce gene tree discordance in target enrichment data

Abstract: The analysis of target enrichment data in phylogenetics lacks optimization toward using paralogues for phylogenetic reconstruction. We developed a novel approach of detecting paralogues and utilizing them for phylogenetic tree inference, by retrieving both ortho‐ and paralogous copies and creating orthologous alignments, from which the gene trees are built. We implemented this approach in ParalogWizard and demonstrate its performance in plant groups that underwent a whole genome duplication relatively recently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 83 publications
(117 reference statements)
1
6
0
Order By: Relevance
“…In our case, the Angiosperms353 ML phylogenetic reconstruction recovered a similar topology to our bait set (Figure 4), but displayed many very short branches, especially in the already hard-to-resolve southern clade (clade I in Cosacov et al, 2009). As a result, some studies have started to develop alternative bait sets that would recover infra-group variation (e.g., Ufimov et al, 2022). This study both develops a Calceolariaceae-specific bait set, and importantly, makes a significant contribution to this literature by developing a pipeline that can be used in other groups of closely related plants.…”
Section: Workflow and Bait Setsupporting
confidence: 61%
“…In our case, the Angiosperms353 ML phylogenetic reconstruction recovered a similar topology to our bait set (Figure 4), but displayed many very short branches, especially in the already hard-to-resolve southern clade (clade I in Cosacov et al, 2009). As a result, some studies have started to develop alternative bait sets that would recover infra-group variation (e.g., Ufimov et al, 2022). This study both develops a Calceolariaceae-specific bait set, and importantly, makes a significant contribution to this literature by developing a pipeline that can be used in other groups of closely related plants.…”
Section: Workflow and Bait Setsupporting
confidence: 61%
“…Johnson et al 2019; Nikolov et al 2019). However, strict exclusion of all genes with paralogs is rarely possible or limits the number of potential target genes considerably when the taxa of interest have undergone WGDs in their recent history, which is common for plants, and many genes have paralogs (Ufimov et al 2022). Subsequent filtering for paralogs during analysis of the sequencing data is often conducted, for example in one of the most commonly used target enrichment analysis pipelines, HybPiper (Johnson et al 2016), based on sequence length and similarity.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of genes consisting of both orthologs and paralogs may result in accurate species tree reconstruction when methods accounting for incomplete lineage sorting (Yan et al 2021) or gene duplications (Zhang et al 2020) are used. Alternatively, detection of paralogs can be conducted based on patterns of sequence divergence between alleles and paralogs within a sample to obtain separate alignments for orthologs and paralogs from older WGDs, which may contain phylogenetic signal and thus contribute to overall better phylogenetic resolution at the species tree level by including more gene trees (Ufimov et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Angiosperm genomes often contain a large number of paralogous genes due to the prevalence of polyploidy or whole-genome duplication events in the evolutionary history of plants ( Soltis et al., 2009 ; Jiao et al., 2011 ; Panchy et al., 2016 ). Although target capture bait kits such as Angiosperms353 are designed to target low- or single-copy loci, paralogous copies of targeted loci are present in many lineages ( Nauheimer et al., 2021 ; Smith and Hahn, 2021 ; Ufimov et al., 2022 ). Paralogous loci can violate the assumption of homology in phylogenetic analysis and confound resulting trees, and so are commonly removed in analyses (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, the retention and identification of paralogous loci in phylogenetic studies has been shown to be highly valuable for maximizing the amount of informative data, explaining discordance between gene trees, and in pinpointing where genome duplication events such as ancient polyploidization and hybridization have played an important role in the evolution of lineages (e.g. Nauheimer et al., 2021 ; Morales-Briones et al., 2021 ; Smith and Hahn, 2021 ; Ufimov et al., 2022 ). Identification, characterization and analysis of paralogy is now possible with target capture sequencing, making it a promising method for improving the resolution of relationships within Sapindales, and for gaining new insight into the role of gene duplication events during the evolution of the order.…”
Section: Introductionmentioning
confidence: 99%